Working Out the Kinks: Testing the Feasibility of an Electronic Pain Diary for Adolescents with Arthritis. (2008) - Stinson, Jennifer N; Petroz, Guy C; Stevens, Bonnie J; Feldman, Brian M; Streiner, David; McGrath, Patrick J; Gill, Navreet
Abstract : BACKGROUND: Current approaches to evaluating pain in children with chronic arthritis suffer from methodological problems. A real-time data capture approach using electronic diaries has been proposed as a new standard for pain measurement. However, there is limited information available regarding the development and feasibility of this approach in children. OBJECTIVES: The aim of the present study was to pilot test the e-Ouch electronic pain diary in terms of compliance and acceptability in adolescents with arthritis to further refine the prototype. METHODS: A descriptive study design – with two iterative phases of testing, modifying the prototype and retesting – was used. A purposive sample of 13 adolescents with mild to severe pain and disability was drawn from a large rheumatology clinic in a university-affiliated pediatric tertiary care centre in Canada over a four-week period in December 2004. Participants were signalled with an alarm to use the diary three times per day for a two-week period. Adolescents completed an electronic diary acceptability questionnaire. RESULTS: Overall mean compliance rates for phases 1 and 2 were 72.9% and 70.5%, respectively. Compliance was affected by the timing of data collection and technical difficulties. Children rated the diary as highly acceptable and easy to use. Phase 1 testing revealed aspects of the software program that affected compliance, which were subsequently altered and tested in phase 2. No further technical difficulties arose in phase 2 testing. CONCLUSIONS: Feasibility testing is a crucial first step in the development of electronic pain measures before use in clinical and research practice.